From Pledges to Profits? Stock Market Reactions to Net-Zero Commitments in Norway, Sweden and Finland - Repo, Eemil (My University, 2025)
Climate change and growing expectations for corporate responsibility are putting more pressure on companies to support global sustainability goals. Particularly in ESG-mature markets such as those in the Nordic region, net-zero commitments have emerged as a one key strategic response to achieve sustainability goals. This thesis examines whether investors value corporate net-zero commitments in ESG-mature markets, focusing on companies based in Norway, Sweden, and Finland. As net-zero commitments have become a central part of corporate climate strategy, particularly in Europe, it remains uncertain how financial markets interpret and react to such announcements. To address this, an event study methodology is employed to analyze short-term abnormal returns surrounding 22 net-zero announcements made between 2019 and 2024. In addition, an OLS regression model is used to explore which firm- and event-specific factors explain the variation in market reactions. The results show that, on average, net-zero commitments are associated with positive and statistically significant cumulative abnormal returns. These findings suggest that investors in ESG-mature markets perceive climate pledges as credible signals of long-term strategic intent. Furthermore, firms with more ambitious targets and higher ESG scores tend to experience stronger market reactions, indicating that both the quality of the commitment and prior environmental performance matter. In contrast to prior studies in markets with less mature ESG frameworks, which have found either negative or insignificant market responses, this thesis finds opposite reactions. Overall, this thesis contributes to the emerging literature on climate-related financial disclosure by providing evidence that, in well-developed ESG countries, corporate climate commitments can be positively valued by investors. Future research could examine the content and concrete measures of the commitments in more detail, as well as track their long-term impacts on corporate performance and investor confidence.

Ilmastonmuutos ja kasvavat odotukset yritysten vastuullisuudesta asettavat yhä enemmän painetta yrityksille tukea globaaleja kestävän kehityksen tavoitteita. Erityisesti ESG:n osalta kehittyneillä markkinoilla, kuten Pohjoismaissa, nettonollasitoumukset ovat nousseet yhdeksi keskeiseksi strategiseksi keinoksi näiden tavoitteiden saavuttamisessa. Tämä tutkielma käsittelee, arvostavatko sijoittajat yritysten nettonollasitoumuksia kehittyneillä ESG-markkinoilla, keskittyen Norjassa, Ruotsissa ja Suomessa toimiviin yrityksiin. Vaikka nettonollasitoumuksista on tullut keskeinen osa yritysten ilmastostrategiaa etenkin Euroopassa, on yhä epäselvää, miten rahoitusmarkkinat tulkitsevat ja reagoivat tällaisiin sitoumuksiin. Tätä varten hyödynnetään tapahtumatutkimusta, jolla tarkastellaan lyhyen aikavälin poikkeavia tuottoja 22 hiilineutraaliustavoitteen julkistuksen yhteydessä vuosina 2019–2024. Lisäksi käytetään pienimmän neliösumman regressiomallia (OLS) selvittämään, mitkä yritys- ja tapahtumatason tekijät selittävät markkinareaktioiden vaihtelua. Tulokset osoittavat, että nettonollasitoumuksiin liittyy keskimäärin positiivisia ja tilastollisesti merkitseviä kumulatiivisia epänormaaleja tuottoja. Nämä havainnot viittaavat siihen, että sijoittajat kehittyneillä ESG-markkinoilla pitävät nettonollasitoumuksia uskottavina viesteinä pitkäjänteisestä strategisesta aikomuksesta verrattuna muihin maihin. Lisäksi yritykset, joilla on kunnianhimoisemmat tavoitteet ja korkeammat ESG-pisteet, kokevat voimakkaampia markkinareaktioita, mikä viittaa siihen, että sekä sitoumuksen laatu että aiempi ympäristösuorituskyky vaikuttavat tuloksiin. Toisin kuin aiemmat tutkimukset vähemmän kehittyneillä ESG-markkinoilla, joissa markkinareaktiot ovat olleet negatiivisia tai merkityksettömiä, tämä tutkielma löytää päinvastaisia reaktioita. Kaiken kaikkiaan tämä tutkielma tuo lisänäyttöä ilmastoon liittyvästä taloudellisesta raportoinnista ja osoittaa, että ESG:n kannalta hyvin kehittyneissä maissa ilmastositoumuksia voidaan arvostaa positiivisesti sijoittajien toimesta. Tulevaisuuden tutkimuksessa voitaisiin tarkastella laajemmin sitoumusten sisältöä ja konkreettisia toimenpiteitä, sekä seurata
Keywords: event study, stock market reaction, net-zero commitments, tapahtumatutkimus, osakemarkkinareaktio, nettonollasitoumukset